In silico studies on the interaction between bioactive ligands and ALK5, a biological target related to the cancer treatment. Issue 9 (1st September 2016) - Almeida, Michell O.; Trossini, Gustavo H. G.; Maltarollo, Vinícius G.; Silva, Danielle da C.; Honorio, Kathia M.
Abstract : Studies have showed that there are many biological targets related to the cancer treatment, for example, TGF type I receptor (TGF-βRI or ALK5). The ALK5 inhibition is a strategy to treat some types of cancer, such as breast, lung, and pancreas. Here, we performed CoMFA and CoMSIA studies for 70 ligands with ALK5 inhibition. The internal validation for both models ( q 2 LOO  = 0.887 and 0.822, respectively) showed their robustness, while the external validations showed their predictive power (CoMFA: r 2 test  = 0.998; CoMSIA: r 2 test  = 0.975). After all validations, CoMFA and CoMSIA maps indicated physicochemical evidences on the main factors involved in the interaction between bioactive ligands and ALK5. Therefore, these results suggest molecular modifications to design new ALK5 inhibitors.